Tożsamość Białorusinów - Kakareko, Ksenia (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
Belarussian identity seems to be a regional identity rather than a national one. The process of the emergence of national identity has not yet been completed, and it seems to be taking a different route inWestern Belarussia, in particular in the Grodno region, another one in Minsk, and yet another one in Eastern Belarussia. Therefore, the distinctiveness of Belarussians from the Russians can only be evidenced by folk customs and songs, which are slowly becoming a thing of the past as the older generation passes away. They have become a mere ethnographic curiosity which does not attract much interest among the local audience, anyway.